Toolbox: Gaussian comparison on Eucledian balls - Andzhey Koziuk; Vladimir Spokoiny (Humboldt-Universität zu Berlin, International Research Training Group 1792 "High Dimensional Nonstationary Time Series", 2018)
In the work a characterization of difference of multivariate Gaussian measures is found on the family of centered Eucledian balls. In particular, it helps to derive (xx see paper).
Keywords: C00; 330; multivariate Gaussian measure; Kolmogorov distance; Gaussian comparison